KETIMPANGAN PEMBANGUNAN EKONOMI REGIONAL KALIMANTAN - Mutia Madina; Muzdalifah M (Ecoplan, 2020)
Abstrack- This research was conducted to (1) Know the economic development in Kalimantan region from 2011 to 2018; (2) Analyze the effect of regional share, proportional shift, and competitive shift on inequality in economic development. The data analysis technique used are: the first, Klassen typology analysis as a descriptive approach, and the second, the panel data regression analysis with random effect model estimation as a quantitative research approach. This research uses secondary data. Klassen's typological analysis showed the results that not all the provinces have positive growth every year. The analysis of panel data regression showed the results that the regional share and the competitive shift do not affect the development disparities which occurred in Kalimantan. Meanwhile, the proportional shifts affect the imbalance of development which occurred in Kalimantan region. Keywords: Economic Development Inequality, Klassen Typology, Regional Share, Proportional Shift, Competitive Shift. Abstrak- Penelitian ini dilakukan untuk (1) Mengetahui perkembangan perekonomian region kalimantan mulai tahun 2011 sampai 2018; (2) Menganalisis pengaruh regional share, proportional shift, dan competitive shift terhadap ketimpangan pembangunan ekonomi.Teknik analisa data yang digunakan yaitu pertama analisis tipologi klassen sebagai pendekatan deskriptif dan yang kedua yaitu analisis regresi data panel dengan estimasi random effect model sebagai pendekatan penelitian kuantitatif. Penelitian ini menggunakan data sekunder.Analisis tipologi klassen menunjukkan hasil bahwa tidak semua provinsi memiliki pertumbuhan positif setiap tahunnya. Analisis regresi data panel menunjukkan hasil bahwa regional share dan competitive shift tidak mempengaruhi ketimpangan pembangunan yang terjadi di regional Kalimantan. Sedangkan proportional shift mempengaruhi ketimpangan pembangunan yang terjadi di regional Kalimantan. Kata kunci : Ketimpangan Pembangunan Ekonomi, Tipologi Klassen, Regional Share, Proportional Shift, Competitive Shift.